THE ROLE AND CHALLENGES OF HONORARY TEACHERS IN THE NATIONAL EDUCATION SYSTEM: A LITERATURE REVIEW - Didik Cahyono; Aslan Aslan (Adisam Publisher, 2025)
Honorary teachers have a strategic role in supporting the national education system, especially in fulfilling the need for teaching staff in areas that lack human resources. However, this role is often faced with challenges such as poor welfare, lack of career security and limited access to professional competence development. This literature review outlines the important contribution of honorary teachers to education and the financial and structural barriers they face. Solving these problems requires collaboration between the government, the community and other stakeholders, especially in formulating more inclusive policies to improve the welfare and quality of the honorary teaching profession. With optimal support, honorary teachers can continue to make maximum contributions to the achievement of national education goals.